UV CROSS-LINKED DONOR CORNEAS FOR PENETRATING KERATOPLASTIES IN CORNEAL PERFORATIONS - Z. I. Moroz; B. E. Malyugin; M. V. Gorochova; E. V. Kovschun (Офтальмохирургия, 2015)
Purpose. To asses the results of penetrating keratoplasty utilizing the crosslinked donor corneas in patients with corneal perforations.Material and methods. Penetraiting keratoplasty was performed in 35 patients. All donor corneal grafts preserved in Borzenok-Moroz median were crosslinked with the help of riboflavin/UV-A irradiation. The follow-up was up to 36 months.Results. Clear corneal grafts were observed in 11 patients (11 eyes), partially clear – in 24 patients (24 eyes). Complete epithelization was seen from 3rd till 14th days after the surgery. No inflammatory complications were observed.Conclusions. The crosslinked donor corneas showed improved mechanical properties and the ability to withstand the corneal melting in the postoperative period. This method potentially reduces the reccurence of cornea fistula and necessity of the secondary keratoplasty.